Neural Responses of Acupuncture for Treating Functional Dyspepsia: An fMRI Study - Dong, Xiaohui; Yin, Tao; Yu, Siyi; He, Zhaoxuan; Chen, Yuan; Ma, Peihong; Qu, Yuzhu; Yin, Shuai; Liu, Xiaoyan; Zhang, Tingting; Huang, Liuyang; Lu, Jin; et al. (Frontiers in Neuroscience, 2022)
Different acupoints have similar therapeutic effects, which is a common phenomenon in acupuncture clinic practice. However, the underlying mechanism remains unclear. This study aimed to investigate the similarities and differences in cerebral activities elicited by puncturing at CV12/ST36, the two most commonly used acupoints in the treatment of gastrointestinal diseases, so as to partly explore the mechanism of the different acupoints with similar effects. Thirty-eight eligible functional dyspepsia (FD) patients were randomly assigned into group A (CV12 group) and group B (ST36 group). Each patient received five acupuncture treatments per week for 4 weeks. The symptom index of dyspepsia (SID) and Nepean dyspepsia index (NDI) were used to assess the efficacy. The functional magnetic resonance imaging (fMRI) scans were performed to detect the cerebral activity changes at the baseline and the end of the treatment. The results demonstrated that:1) improvements of NDSI, NDLQI, SID were found in both group A and group B (p<0. 05). However, there were no significant differences in the improvements of the SID scores, NDSI scores, NDQLI scores between group A and group B (p>0.05); 2) All FD patients showed significantly increased amplitude of low frequency fluctuation (ALFF) in the left postcentral gyrus after acupuncture treatment, and the changes of ALFF in the left postcentral gurus was significantly related to the improvements of SID scores (r=0.358, p=0.041); 3) puncturing at CV12 could significantly decrease the resting-state functional connectivity (rsFC) between the left postcentral gyrus and angular, caudate, middle frontal gyrus (MFG) and cerebellum, while puncturing at ST36 could significantly increase the rsFC between left postcentral gyrus with precuneus, superior frontal gyrus (SFG) and MFG. The results indicated that CV12 and ST36 share the similar therapeutic effect for dyspepsia and the common modulation on the activity of postcentral gyrus in FD patients. However, the modulatory pattern on the functional connectivity of postcentral gyrus were different. Namely, the CV12 mainly aroused the postcentral gyrus-reward network, and the ST36 mainly affect the postcentral gyrus-default mode network circuitry.